2006
DOI: 10.1159/000497607
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between random blood sugar and body mass index in an African population

Abstract: Background: Obesity is the most important modifiable risk factor in the pathogenesis of type-2 diabetes reported in most cross-sectional studies. However, racial factors seem to be important in the relationship between body mass index (BMI) and glucose intolerance. Methods: Three-hundred and seventeen subjects participated in the study. Mean age of subjects was 35.0 + 9.8 years (33.0 + 9.6 among females and 36.2 + 9.6 among males p= 0.1007). Results: Female subjects had significantly higher BMI than their male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
(4 reference statements)
4
9
0
1
Order By: Relevance
“…In females, the correlation was negative in the fasting state and positive in the postprandial state. Our findings agree with those of Bakari et al 31 Other studies showed mixed results. 32,33 In this investigation, lipids concentrations were minimally different between men and women for the measurements performed in the fasting state.…”
Section: Discussionsupporting
confidence: 94%
“…In females, the correlation was negative in the fasting state and positive in the postprandial state. Our findings agree with those of Bakari et al 31 Other studies showed mixed results. 32,33 In this investigation, lipids concentrations were minimally different between men and women for the measurements performed in the fasting state.…”
Section: Discussionsupporting
confidence: 94%
“…The mean BMI found in our study was in the overweight range and is higher in females. This is similar to findings of another study in Nigeria [43]. High average BMI was also demonstrated in many studies in Asian [44][45][46][47][48].…”
Section: Discussionsupporting
confidence: 91%
“…1 The findings of this study suggested that for screening purpose, waist hip ratio had least applicability while those who had blood sugar level have high waist hip ratio. 18,19 During Health camp, all the participants were counseled regarding BMI and hip waist ratio and blood sugar level. Out of 46 participants who recorded high blood sugar, all the participants were advised for follow up in health centers for needed interventions if any.…”
Section: Resultsmentioning
confidence: 99%